Fraud Prevention in the Auto Parts Industry in the ABC Region - Carvalho, Vera Lucia de; Oliva, Eduardo de Camargo (Review of Business Management, 2007)
For many years the fraud cases have been occupying the communication means. One fact that could contribute for this situation are the changes in the organizations are quick and the internal controls tend not follow the same quickness, increasing the practice potential of illicit acts. On the other hand, the technological improvement contributes for information technology, which improves the fraud detection. This investigation had as purpose to verify how the companies practice fraud prevents. For that, it was done a search in some automobile part companies in the ABC region. It was used the stratification criterion, using as basis the Sindipeças list. As result, it was verified that the companies use some internal For many years the fraud cases have been occupying the communication means. One fact that could contribute for this situation are that the changes in the organizations are quick and the internal controls tend not follow the same quickness, increasing the potential practice of illicit acts. On the other hand, the technological improvement contributes for information technology, which improves the fraud detection. This investigation had as purpose to verify how the companies practice fraud prevention. For that, it was done a search in some automobile part companies in the ABC region. It was used the stratification criterion, using as basis the Sindipeças list. As result, it was verified that the companies use some internal controls, however, the subject fraud is not treated with necessary transparence and attention. Besides, the fraud event should be included as business risk. Key-words: Fraud. Prevention. Connivance. Internal controls.